2017
DOI: 10.20944/preprints201706.0050.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strain Wave Acquisition by a Fiber Optic Coherent Sensor for Impact Monitoring

Abstract: A novel fiber optic sensing technology for high frequency dynamics detection is proposed in this paper, specifically tailored for structural health monitoring applications based on strain wave analysis, including both passive impact identification and active Lamb wave monitoring. The sensing solution relies on a fiber optic-based interferometric architecture associated to an innovative coherent detection scheme, which retrieves in a completely passive way the high-frequency phase information of the received op… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Hence, the proposed detection scheme allows one to overcome issues that, until recently, have limited the actual in-situ applicability of this technology that features cost-effectiveness, broadband and high sensitivity. The versatility of the proposed sensing technique has already been widely proven in a variety of engineering contexts, for example, for impact damage diagnostic in aeronautic structures, cavitation onset detection in hydraulic pipes, as well as for predictive maintenance applications in industrial production process (Boffi et al, 2019;Sbarufatti et al, 2017;Ferrario et al, 2016). The sensing scheme can be defined as "integral" as each single measurement provides the sum of the phase difference accumulated by the optical signal during its propagation along the entire length of the sensing cable (ΣΔθ(t)).…”
Section: Interferometric Optical Fibre Sensing Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the proposed detection scheme allows one to overcome issues that, until recently, have limited the actual in-situ applicability of this technology that features cost-effectiveness, broadband and high sensitivity. The versatility of the proposed sensing technique has already been widely proven in a variety of engineering contexts, for example, for impact damage diagnostic in aeronautic structures, cavitation onset detection in hydraulic pipes, as well as for predictive maintenance applications in industrial production process (Boffi et al, 2019;Sbarufatti et al, 2017;Ferrario et al, 2016). The sensing scheme can be defined as "integral" as each single measurement provides the sum of the phase difference accumulated by the optical signal during its propagation along the entire length of the sensing cable (ΣΔθ(t)).…”
Section: Interferometric Optical Fibre Sensing Systemmentioning
confidence: 99%
“…Picarelli et al (2015) report an updated Brillouin frequency shift, that is, a new measurement each 15 min. While for some slow-moving phenomena this sort of temporal resolution would be sufficient, the abrupt nature of shallow failures certainly requires faster monitoring updates that can be easily guaranteed by the proposed interferometric sensor, featuring a wide acquisition bandwidth capability, even up to the MHz, limited only by the adopted ADC (Analog to Digital Converter) sampling board (Sbarufatti et al, 2016). In the presented experiments the sampling frequency of the interferometric sensor, set to 20 kSample/s, was wide enough to yield high precision measurements.…”
Section: Sensor Sensitivitymentioning
confidence: 99%
“…One of the most recent contributions, presented by the authors in a previous work [ 19 ], analyzed a novel fiber-optic based solution for impact detection on an aluminum plate. In this case, the sensor showed promising resulta when compared with commercial PZT sensors.…”
Section: The Coherent Fiber Optic Sensormentioning
confidence: 99%
“…In the second configuration instead, the fiber optic is wound like a spiral, and this latter is set at with respect to the metal surface in order to be adhesively bonded directly onto the structure. This solution was investigated by the authors in a previous work [ 19 ], in which this layout showed promising results in impact detection on an aluminum plate. Regarding this configuration, the advantages include the direct detection of waves traveling in the metal and the possibility to increase the sensitivity by adding more loops to the ring, which, however, could compromise the sensor punctuality in the case of a high number of loops.…”
Section: Fiber Optic Transducermentioning
confidence: 99%
See 1 more Smart Citation